The Application Of Transformative Education In Increasing Students' Social Awareness and Responsibility Senior High School - Erni Suyani; Sinulingga, Neng Nurcahyati (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Transformative education in senior high schools plays an important role in balancing academic achievement with the formation of students' social and religious characters, in line with the perspective of Islamic Religious Education. This study aims to examine how the implementation process of transformative education is carried out at Dharmawangsa High School in Medan City, as well as assess the results achieved in strengthening students' social awareness and responsibility. The research used a qualitative approach with descriptive methods. Data were obtained through interviews, observations, and documentation, then validated using source triangulation and member checks to ensure credibility. The results show that transformative education is successfully integrated in the curriculum through social and religious value-based learning, which encourages students' active involvement in social activities such as fundraising, community empowerment, and environmental preservation. On the other hand, the main challenges arise from the dominance of the academic paradigm that often shifts the priority of social character development, the limited role of teachers outside the principal, and the lack of maximum parental involvement. The implications of this research emphasize the need for synergy between schools, teachers, parents and communities so that transformative education is sustainable and contextual to culture and religious values. The recommendations in this study are the need for a more systematic curriculum design based on Islamic Religious Education values and strengthening collaborative strategies across parties to produce graduates who excel academically while caring socially.